Pengaruh Pembiayaan Terhadap Profitabilitas (ROA) Pada Bank Umum Syariah Di Indonesia (2017-2022) - Nungcahyani, Suci; Wahyudi, Agung (ITB AAS INDONESIA Surakarta, 2024)
This study aims to show the effects of mudharaba financing, musharaka financing, and ijara financing as well as partially and stimulants the profitability of Return On Asset (ROA) at Sharia Commercial Banks (BUS) in Indonesia. This study is quantitative research using secondary data in the form of panel data. The population used in the study is 13 Sharia Commercial Banks in Indonesia. Sample collection used a purposive sampling so that 5 bank units according to the criteria with a total of 120 sample data are obtained. As for data analysis techniques using model selection methods, classical assumption tests, panel data regression, and hypothesis tests. The results of the research show that partial mudharaba financing has no effect and is not significant on ROA on BUS. Musyaraka financing has a positive and significant effect on ROA in BUS. Ijarh financing has a negative and significant effect on ROA on BUS. Meanwhile, the stimulant financing of mudharaba, musyaraka, and ijara has a significant effect on ROA on BUS.